2011
DOI: 10.1016/j.jretconser.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Supermarket consumers and gender differences relating to their perceived importance levels of store characteristics

Abstract: a b s t r a c tFamily grocery shopping is the accepted domain of women; however, modern social and demographic movements challenge traditional gender roles within the family structure. Men now engage in grocery shopping more freely and frequently, yet the essence of male shopping behaviour and beliefs present an opportunity for examination. This research identifies specific store characteristics, investigates the perceived importance of those characteristics and explores gender, age and income differences that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 52 publications
5
42
1
Order By: Relevance
“…In addition, Lockyer (2003) found a significant gender difference in hotel cleanliness perceptions with women giving cleanliness a much higher importance rating than did males. A gender difference was also found in the perceived importance of cleanliness and hygienic practices in Australian supermarkets (Mortimer & Clarke, 2011) Women shoppers perceived store cleanliness and hygienic practices (food handling) to be more important than men (Mortimer & Clarke, 2011). A study by Borchgrevink et al (2013) found that women engaged in proper handwashing behavior significantly more than men, and Kim et al 2013found a significant gender difference in indoor environmental quality satisfaction such that women were less satisfied with building and workplace cleanliness.…”
Section: Demographic Differencesmentioning
confidence: 99%
“…In addition, Lockyer (2003) found a significant gender difference in hotel cleanliness perceptions with women giving cleanliness a much higher importance rating than did males. A gender difference was also found in the perceived importance of cleanliness and hygienic practices in Australian supermarkets (Mortimer & Clarke, 2011) Women shoppers perceived store cleanliness and hygienic practices (food handling) to be more important than men (Mortimer & Clarke, 2011). A study by Borchgrevink et al (2013) found that women engaged in proper handwashing behavior significantly more than men, and Kim et al 2013found a significant gender difference in indoor environmental quality satisfaction such that women were less satisfied with building and workplace cleanliness.…”
Section: Demographic Differencesmentioning
confidence: 99%
“…Despite Hollywood et al (2016), Nakamura et al (2015) and Albright (2015) confirming a balance among healthy and less healthy promotions, it is interesting to discover consumers' perceptions on the healthfulness of promotions being skewed more prevalently towards less healthy food items. The observance of a greater percentage of males reporting they were unsure about the balance of promotions may be explained by Mortimer and Clarke (2011), who find males take less time to shop and are less likely to comparison shop for the best deal and therefore they may be less observant of promotions and the retail environment.…”
Section: Frequency Of Shoppingmentioning
confidence: 99%
“…Women are affected by the discounts and offers (Business Research, 2010) as well as the product attributes in making smart buying decisions (Levy&Christina, 2004, p.322). The woman also are interested in shopping groups and friendly relationships with others in the searching information, and she uses pricing, quality and cleaning level in the store (Mortimer & Clarke, 2011) , but the consumer Women prefer the price more than quality (Srinivasan & Srivastava, 2015). The high level of convincing of the goods purchased and the extra services such as credit, transportation and free shipping are factors enhance the loyalty level of consumer woman (Srinivasan et.…”
Section: 2the Women's Response To the Price Discountsmentioning
confidence: 99%